1991
DOI: 10.1128/aem.57.12.3541-3546.1991
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Propanediol production by Escherichia coli expressing genes from the Klebsiella pneumoniae dha regulon

Abstract: The dha regulon in KkebsieUa pneumoniae enables the organism to grow anaerobically on glycerol and produce 1,3-propanediol (1,3-PD). Escherichia coli, which does not have a dha system, is unable to grow anaerobically on glycerol without an exogenous electron acceptor and does not produce 1,3-PD. A genomic library of K. pneumoniae ATCC 25955 constructed in E. coli AG1 was enriched for the ability to grow anaerobically on glycerol and dihydroxyacetone and was screened for the production of 1,3-PD. The cosmid pTC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(56 citation statements)
references
References 23 publications
3
53
0
Order By: Relevance
“…They followed the same oscillation patterns as CO 2 evolution and growth rate (data not shown). A possible reason for the simultaneous oscillations of these three enzymes may be that their genes belong to one and the same regulon, dha (Forage and Lin, 1982;Tong et al, 1991), and thus subject to the same regulations. The magnitudes of the oscillations of these enzymes corresponded to their concentration levels under steady state: GDH displayed a minimum of 2.3 and a maximum of 4.6 U/mg protein; PDOR a minimum of 1.2 and a maximum of 4.3 U/mg protein; and GDHt a minimum of 0.8 and a maximum of 2.0 U/mg protein.…”
Section: In Vitro and In Vivo Enzyme Activities Under Sustained Oscilmentioning
confidence: 99%
See 1 more Smart Citation
“…They followed the same oscillation patterns as CO 2 evolution and growth rate (data not shown). A possible reason for the simultaneous oscillations of these three enzymes may be that their genes belong to one and the same regulon, dha (Forage and Lin, 1982;Tong et al, 1991), and thus subject to the same regulations. The magnitudes of the oscillations of these enzymes corresponded to their concentration levels under steady state: GDH displayed a minimum of 2.3 and a maximum of 4.6 U/mg protein; PDOR a minimum of 1.2 and a maximum of 4.3 U/mg protein; and GDHt a minimum of 0.8 and a maximum of 2.0 U/mg protein.…”
Section: In Vitro and In Vivo Enzyme Activities Under Sustained Oscilmentioning
confidence: 99%
“…In this work, we report on experimental results concerning the effects of culture conditions on the in vitro and in vivo activities of glycerol dehydrogenase, glycerol dehydratase, and 1,3-propanediol oxidoreductase under both steadystate and oscillation conditions. The genes for these three enzymes and the enzyme dihydroxyacetone kinase are encoded in one and the same regulon named dha (Forage and Lin, 1982;Tong et al, 1991) and have been cloned and sequenced for K. pneumoniae (Cameron et al, 1998;Tong et al, 1991) and C. freundii (Daniel and Gottschalk, 1992;Daniel et al, 1995). The transient behavior of the culture after step changes of substrate concentration in medium is also studied.…”
Section: Introductionmentioning
confidence: 99%
“…Native E. coli does not ferment glycerol to 1,3-PD. We have shown that E. coli transformed with the K. pneumoniae dhaT and dhaB genes is able to coferment glycerol and glucose (8,12). The glycerol is converted primarily to 1,3-PD, and the glucose is used for growth and regeneration of reducing potential.…”
Section: Production Of 13-propanediolmentioning
confidence: 99%
“…In addition, coenzyme-B 12 (5 mg/L) was added at the beginning of each fermentation in darkness to prevent light inactivation. No 1,3-PD was detected in the fermentation broth after 48 h. To determine if the enzymes were expressed, the fermentation was repeated, but this time without coenzyme-B 12 , which has been reported to contribute to the irreversible inactivation of glycerol dehydratase (18,19). After 36 h, the cells were harvested and crude cell extracts were made by vortexing with glass beads according to the method of Jazwinski (20).…”
Section: Production Of 13-propanediolmentioning
confidence: 99%
See 1 more Smart Citation